A Case of Neglected Posterior Fracture Dislocation of the Shoulder Treated With Greater Tuberosity Osteotomy - Masashi Koide; Satoshi Tateda; Sayaka Miyasaka; Akihiro Yasuyama; Yoichi Sasaki; Mika Abe (Case Reports in Orthopedics)
Posterior dislocation of the shoulder joint is a rare condition. It is often misdiagnosed owing to a lack of evident clinical features compared with anterior shoulder dislocation, and inappropriate radiological examination. We present a case of chronic posterior fracture dislocation treated with greater tuberosity osteotomy. A 66-year-old man was injured in a fall while carrying a drone. He was referred to our hospital following 3 months of conservative treatment at a nearby clinic, without reduction of the posterior dislocation. Physical examination revealed a prominent reduction in shoulder joint range of motion and shoulder pain. Radiological examination revealed posterior shoulder dislocation associated with greater tuberosity malunion and a small bone fracture of the posterior portion of the glenoid. Open reduction and internal fixation, including greater tuberosity osteotomy, were performed. Although subluxation of the posterior dislocation persisted postoperatively, the humeral head gradually returned to its centric shoulder joint position owing to rotator cuff force coupling. At 24-month follow-up, the patient showed excellent shoulder results.